UNDERSTANDING THE E-WALLET USERSâ BEHAVIOR (CASE: GOPAY) - Astri Ramadhina, Farah
There is a great potential for growth in the digital payment acceptance market in Indonesia, which makes it a promising country for the mobile wallet industry. Indonesia is one of countries that are rapidly shifting away from a cash-based economy and toward one that relies more on digital payments. The adoption of mobile wallets in Indonesia, a country with a remarkably low credit card penetration rate, is drawing new consumers of digital commerce at a rapid pace. The number of mobile or electronic wallets is growing as a result of the increasing popularity of digital payment methods as well as the massive change in the consumers preferences of payment systems. This creates a competition between e-wallet providers with each offering similar payment services. GoPay, one of the five largest e-wallet providers in the Indonesian market is contributing in the payment industry with its competitive advantage in the middle of the fierce competition. This study aimed to gather profound information of the current consumers behavior of mobile wallets, the characteristics, and motivations of utilizing it in order to create a strategy for the business. An online survey was conducted, and a total of 263 respondents participated and submitted their responses. The data was gathered from primary and secondary sources. This study used descriptive research to describe the outcomes of the data. For the purpose of gaining insight into the users' and GoPay's perspectives, qualitative data was also collected along with the quantitative. The findings of this study revealed that users of different age generations had substantially different behavior. According to the findings of this study, users typically have more than two electronic wallets installed on their device and use them more than once per week. Moreover, it identified that the main reason users use e-wallet was due to the need for digital payment. Thus, this study suggests that the company can maintain its effort to be the most widely available payment platform to fulfill the demand of digital payment. The findings can be used to have a better understanding of the latest user’s behavior of using mobile wallets.